PEDAGOGICAL COMMUNICATION’S ROLE AND IMPORTANCE IN THE DEVELOPMENT OF STUDENTS’ PROFESSIONAL THINKING - Kurbanova , Gulnoz (Eurasian Journal of Academic Research, 2022)
It is impossible to imagine human development, socialization, formation of an individual as a person, his connection with society without communication. Communication is also a unique need. As the Polish psychologist E. Melibruda [1, p.256] said, interpersonal relationships are as important to us as air. In infancy and adolescence, communication is embodied as an activity that directly affects the leading activity, that is, the formation of new psychological characteristics.